Role of Composition to Degree of Conversion of Bulk Fill Composite Resins - Sefty Aryani Harahap; Yosi Kusuma Eriwati (Jurnal Material Kedokteran Gigi, 2017)
A recent technology of Bulk fill composite resin has been developed to save manipulation time. Bulk fill composite resinhas been claimed to have depth of cure up to 4 mm with a high degree of conversion. This paper will evaluate the role of bulk fill composite resin’s composition in increasingits degree of conversion. The degree of conversion is the percentage of carbon double bonds that were converted into single bonds as a result of polymerization. It is determined by its composition that contained filler, resin matrix and the photoinitiator. With the development and modifications of the composition, the bulk fill compositeresin can be obtained a high degree of conversion so that the expected properties can be achieved.